PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO MATAKULIAH BISSINESS ENGLISH I BERBASIS MOBILE E- LEARNING DI POLITEKNIK LP3I JAKARTA KAMPUS PULOGADUNG - Prabandari, Sari (POLITEKNIK LP3I JAKARTA, 2019)
The purpose of this research is how to increase the learning outcomes bussiness english which is still below the expected standard of competence. Based on preliminary research has been done using models Borg and Gall, obtained information / data that is required instructional media to support the learning process. To develop this audio media, Dick and Carey models used until formative test step.The expected learning media can help students to learn independently to take advantage of technological devices commonly accessible everyday, anywhere and anytime is a mobile phone. Research methods research and development is to develop instructional media audio Bussiness English 1 based mobile learning.The results achieved in this study were produced an media audio instructional-based mobile learning, and after the stages of development of Dick and Carey model obtained value of learning outcomes of students who are above the expected standard competence. Posttest increase of 28.2% from the results of pre-test has been done before. Keywords: audio, develop, media, mobile phone, mobile learning